Perishable state-making: Vegetable trade between self-governance and ethnic entitlement in Jigjiga, Ethiopia - Fana Gebresenbet (Danish Institute for International Studies (DIIS), 2018)
This working paper, based on a study of the vegetable trade in Jigjiga, the capital of Ethiopia's Somali region, argues that in the absence of the state a market can be self-governing with norms being established through long years of practice and interaction. Wholesalers located in Jigjiga hold the legitimate governing authority in this self-governing trade that comes with bearing most of the risk. The vegetable trade encompasses a range of actors that includes agents at sites of production, transporters, wholesalers and retailers of various scales. The state makes only minimal interventions in this trade. My findings indicate that state effects of trade are contingent on the nature of the commodity in question. Durability versus perishability of (agricultural) produce as well as its monetary value invite different degrees of state intervention. A range of practical norms guide vegetable trading. Some are borne out of the instrumental role of ethnicity in Ethiopia's and, more importantly, in Somali region's economic and political landscapes, with others are governed by the material conditions of vegetables. The pattern of accumulation indicates ethnic stratification. Oromo women from adjacent highlands and widowed Somali women dominate the lowest rungs of the ladder. Retailers, mainly using trust-based exchange with wholesalers, come from Amhara, Oromo and Somali backgrounds. As one ascends the capital ladder in local vegetable trading, particularly among wholesalers, the Somalis dominate. This paper thus argues that vegetable trade's state effects are impacted by the material conditions imposed by the commodity, and have differentiated consequences following the role ethnicity plays in Ethiopia's politics of entitlement.
Keywords: 330